1999
DOI: 10.1681/asn.v1061303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Saline, Albumin, or Hydroxyethylstarch on Blood Volume during Combined Ultrafiltration and Hemodialysis

Abstract: Abstract. It is generally advocated to use saline or albumin infusions during symptomatic hypotension during dialysis. However, because of their side effects and/or costs, they are of limited use. Hydroxyethylstarch (HES), a synthetic colloid with a long-standing volume effect, is used in the management of hypovolemia. In this study, the efficacy of three fluids (isotonic saline [0.9%], albumin [20%], and HES [10%]) was assessed during three treatment sessions with combined ultrafiltration and hemodialysis, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As summarized in Table 3, clinical trials that have specifically assessed the use of intravenous albumin for mitigating hypotension and/or augmenting ultrafiltration (47)(48)(49)(50)(51) have generally been small (with all having been conducted at single centers) and are heterogeneous with respect to the intervention (iso-or hyperoncotic albumin, volume, and timing/indications for administration) and outcomes assessed. In the largest trial involving maintenance HD, Knoll et al (48) sought to assess the use of isooncotic (5%) albumin infusion versus normal saline for the acute management of IDH during maintenance HD.…”
Section: Effectiveness Of Intravenous Albumin For Patients Receiving ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 3, clinical trials that have specifically assessed the use of intravenous albumin for mitigating hypotension and/or augmenting ultrafiltration (47)(48)(49)(50)(51) have generally been small (with all having been conducted at single centers) and are heterogeneous with respect to the intervention (iso-or hyperoncotic albumin, volume, and timing/indications for administration) and outcomes assessed. In the largest trial involving maintenance HD, Knoll et al (48) sought to assess the use of isooncotic (5%) albumin infusion versus normal saline for the acute management of IDH during maintenance HD.…”
Section: Effectiveness Of Intravenous Albumin For Patients Receiving ...mentioning
confidence: 99%
“…In theory, the use of hyperoncotic albumin has a stronger theoretical foundation for use in KRT than iso-oncotic albumin given its potential to result in greater fluid shifts from the interstitium to the intravascular space. In general, the small studies that assessed the use of hyperoncotic albumin did suggest that it led to significant hemodynamic improvements (47,4951) (see Table 3). The largest trial that assessed the effect of hyperoncotic albumin for prevention (rather than treatment) of IDH included 65 patients starting HD for either AKI or as maintenance HD who were randomized to 100 ml of normal saline versus 25% albumin prior to HD and then alternated between the two fluids for up to six subsequent HD sessions (249 sessions were included).…”
Section: Effectiveness Of Intravenous Albumin For Patients Receiving ...mentioning
confidence: 99%
“…8 Albumin did not show a significant benefit in terms of improved clinical outcomes over alternatives in patients undergoing renal replacement therapy in several crossover trials. [23][24][25][26] A retrospective, single-center, chart review over a 6-month period in Germany found an appropriate indication for albumin in 67.7% of patients using broader criteria than our study, particularly, uses of albumin that were considered appropriate included acute respiratory distress syndrome, cirrhotic ascites, hypovolemia, nephrosis or nephropathy, fluid resuscitation in septic shock in combination with crystalloid therapy, cardiovascular surgery, large volume paracentesis greater than five liters, hepatorenal syndrome, and therapeutic plasma exchange. 27 Appropriate indications in the study by John et al were based on FDA-approved indications, the Surviving Sepsis Campaign, and the indications considered appropriate by Buckley et al 12,27 A retrospective audit in 2017 of Ontario data by Rodrigues et al found that albumin was used for nonevidence-based indications 78% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…The ALBIOS trial comparing a combination of albumin and crystalloids to crystalloids alone in 1818 patients with sepsis or septic shock did not demonstrate a difference in 28‐day (RR 1.0; 95% CI 0.87–1.14) or 90‐day mortality (RR 0.94; 95% CI 0.85–1.05) 8 . Albumin did not show a significant benefit in terms of improved clinical outcomes over alternatives in patients undergoing renal replacement therapy in several crossover trials 23–26 . A retrospective, single‐center, chart review over a 6‐month period in Germany found an appropriate indication for albumin in 67.7% of patients using broader criteria than our study, particularly, uses of albumin that were considered appropriate included acute respiratory distress syndrome, cirrhotic ascites, hypovolemia, nephrosis or nephropathy, fluid resuscitation in septic shock in combination with crystalloid therapy, cardiovascular surgery, large volume paracentesis greater than five liters, hepatorenal syndrome, and therapeutic plasma exchange 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Among other preventive procedures, the appropriate assessment of volume status and dry weight, increasing the frequency and/or the duration of hemodialysis sessions, lowering the dialysate temperature, and reducing ultrafiltration and antihypertensive drugs are enumerated [ 13 , 14 , 15 ]. The occurrence of IDH may require infusion of fluids such as crystalloids or colloids [ 16 ]. Glucose solutions are of special interest because, contrary to NaCl solutions, the osmotic effect of glucose solutions dissipates as soon as glucose is disposed and metabolized.…”
Section: Introductionmentioning
confidence: 99%